معالجة الشروق اليومي لظاهرة العنف المدرسي دراسة تحليلية - بقاص, إسلام (University of Eloued جامعة الوادي, 2017)
تهدف دراسة الموضوع المدروس "معالجة ظاهرة العنف المدرسي في الصحافة اليومية المكتوبة" إلى التعرف على مدى تناول الصحافة اليومية المكتوبة موضوع العنف المدرسي ومدى توعية الجمهور المستهدف بالمادة الإعلامية. تمت صياغة التساؤل الرئيسي على النحو التالي: ما هو مقدار حجم اهتمام صحيفة الشروق بموضوع العنف المدرسة، وما طبيعة تناولها له؟ ويندرج تحت هذا التساؤل الأسئلة الفرعية التالية: -ما هو مقدار الأهمية والمساحة التي خصصتها صحيفة الشروق اليومي في معالجة ظاهرة العنف المدرسي؟ -ما هي مختلف الأنواع الصحفية التي تم اعتمادها في صحيفة الشروق اليومي في معالجتها لظاهرة العنف المدرسي؟ - ما هي مختلف مصادر المعلومة التي اعتمدت عليها صحيفة الشروق اليومي في عرض ظاهرة العنف المدرسي؟ - ما هي العوامل المؤدية للعنف المدرسي الممارس حسب نشر في صحيفة الشروق اليومي ؟ - ما هي مختلف أشكال العنف المدرسي حسب ما ورد في صحيفة الشروق اليومي؟ - ما هي الآثار المترتبة عن ظاهرة العنف المدرسي كما هو وارد في صحيفة الشروق اليومي؟ - ما هي الأساليب الإقناعية المستخدمة أثناء تناول موضوع العنف المدرسي ؟ لقد اعتمدت في دراستي لموضوع "المعالجة الصحفية لظاهرة العنف المدرسي في الصحافة اليومية المكتوبة" على المنهج الوصفي التحليلي، ولجمع البيانات استخدمنا استمارة تحليل مضمون. لقد أسفرت هذه الدراسة عن النتائج التالية: - ركزت الصحيفة في تناولها لموضوع العنف المدرسي على عرض المشكلة العنف المدرسي بشكل سطحي دون التعرض إلى مختلف الاستراتيجيات و الآليات التي تساهم في التخفيف من حدتها، وهذا ما يؤدي إلى تكوين صورة ضبابية أو مشوهة عن واقع هذه الظاهرة لأن فهمها من طرف الجمهور المستهدف بالمادة الإعلامية لا يأت من خلال البنية المعرفية المفاهيمية الكلية، فيتشكل بذلك مدركات كلية ذات دلالات ومعاني واقعية. - تتنوع أشكال العنف المدرسي الممارس والعنف الجسدي من أكثر الأشكال انتشارا وهذا من خلال معالجة صحيفة الشروق لموضوع العنف المدرسي. - تختلف الأسباب المؤدية للعنف المدرسي وحسب ما ورد في صحيفة احتلت الأسباب المدرسية المرتبة الأولى أما المرتبة الثانية فتمثلت في الأسباب النفسية تلتها الأسباب الاجتماعية في المرتبة الثالثة وجاءت الأسباب الأخرى في الأخير. يعتبر صحفيو الشروق أهم مصدر من مصادر المعلومة المتعلقة بالعنف المدرسي والتي تم نشرها على مستوى صحيفة الشروق. - أبدت صحيفة الشروق اهتماما واسعا لموضوع العنف المدرسي وأعطته مساحة كبيرة في معالجتها له، رغم طابعها التجاري الذي يخصص حيزا و فضاء تجاريا اشهاريا - تعتبر صحيفة الشروق موضوع العنف المدرسي ظاهرة ذات بعد أخلاقي أولا وفي المرتبة الثانية ورد بنوع اجتماعي وذلك نظرا لنسب المرتفعة لهذه العنصر حيث أن الجريدة لم تلم بجميع جوانب الموضوع، حيث أنها لم تدرس الموضوع من زاويا أخرى كالأمنية والدينية والاقتصادية وهو ما يعبر عنه عدم توازن جوانب الموضوع. - يؤثر العنف المدرسي بشكل كبير ويخلف الكثير من الآثار خاصة النفسية والجسدية - تم تناول موضوع العنف المدرسي في صحيفة الشروق بطريقة سلبية من خلال ابرز خطوات الظاهرة التي تعد في الأساس ظاهرة سلبية في حد ذاتها بالنسبة لجريدة الشروق. - قامت الصحيفة بتقوية موضوعاتها وذلك بالعمل على وتيرة الاستشهاد بالأمثلة والأحداث كإحدى الإستمالات المنطقية أثناء تناولها لموضوع العنف المدرسي بينما وردت مخاطبة المشاعر في المرتبة الثالثة وعرض النصوص القانونية في المرتبة الرابعة وتقديم الإحصائيات والأرقام المرتبة الخامسة . The purpose of this study is to examine the extent to which the daily press addresses the subject of school violence and the extent to which the target audience is aware of the media material. The main question was formulated as follows: What is the extent of the interest of Echorouk newspaper on the issue of school violence، and what is the nature of it? This question has the following sub-questions: - What is the amount of importance and space allocated by Echorouk daily in dealing with the phenomenon of school violence? - What are the different press types adopted in Echorouk daily in dealing with the phenomenon of school violence? - What are the various sources of information on which the daily Echorouk relied on the phenomenon of school violence? - What are the factors leading to school violence practiced according to the daily newspaper Echorouk? What are the various forms of school violence، according to Echorouk daily? - What are the effects of the phenomenon of school violence as described in the daily newspaper Echorouk? - What are the persuasive techniques used when dealing with school violence? In my study of the subject of "Press Treatment of the Phenomenon of School Violence in the Written Journalism"، I relied on the analytical descriptive approach. To collect the data، we used a content analysis form. This study resulted in the following results: - The newspaper focused on the subject of school violence on the presentation of the problem of school violence superficially without exposure to various strategies and mechanisms that contribute to the mitigation of this، which leads to the formation of a blurry or distorted the reality of this phenomenon because the understanding of the target audience information material Does not come through the cognitive structure of the total conceptual، thus forming the perceptions of a college with real meanings and meanings. - The forms of school violence practiced and physical violence vary from the most widespread forms، and this through the treatment of Echorouk newspaper on the subject of school violence. - The causes of school violence are different. According to the newspaper، the reasons for school violence ranked first. The second place was psychological reasons followed by social reasons in third place. The other reasons were the most important. The level of the daily newspaper. - Echorouk newspaper showed a great interest in the subject of school violence and gave it a large area in dealing with it، despite its commercial nature، which allocates space and commercial space for advertising - Echorouk is considered the subject of school violence is a phenomenon with a moral dimension first، and second in response to the social type، because of the high rates of this element، since the newspaper did not understand all aspects of the subject، as it did not study the subject from another angle، such as security and religious and economic، Aspects of the subject. - School violence affects significantly and leaves a lot of special effects، psychological and physical - The subject of school violence in Echorouk was dealt with in a negative way through the most prominent steps of the phenomenon، which is basically a negative phenomenon in itself for Echorouk newspaper. - The newspaper strengthened its subjects by working on the pace of quoting examples and events as one of the rationalizations while addressing the subject of school violence، while addressing the feelings in third place and presentation of legal texts in fourth place and provide statistics and figures ranked fifth
مذكرة ماستر تخصص دعوة واعلام
Keywords: العنف، صحافة، مدرسي، الشروق، استمالات، قانون، ظاهرة، جريدة; Violence, journalism, school, echorouk, appeals, law, phenomenon, newspaper